Development of local government in the Republic of Kazakhstan at the present stage. (Journal of Economic Research & Business Administration, 2015)
Local government plays important role in the economic , political and legal life of Kazakhstani society , in establishing the institutions of a democratic state . In modern Kazakhstan Local government raised to the level of one of the foundations of the constitutional system . It gives you the opportunity to postpone action on all matters of local importance , thereby stimulating the activity of citizens and providing them with a real sense of ownership to such decisions . In modern conditions important issues become increasingly related to the development of local self-government as one of the institutions of society democratization. Local government in the world is the foundation of regional development. Very briefly about the nature of local government can say that his presence meant that the country , along with the interests of the individual and the state, recognized and guaranteed even local interests – interests associated with the solution of direct support of the population’s vital activity of each individual locality.
Keywords: State bodies; local government; political subdivision; legal regulation; constitution; civil society; elected bodies; maslihat